2022
DOI: 10.1530/eje-21-0716
|View full text |Cite
|
Sign up to set email alerts
|

Updated clinical management guidance during the COVID-19 pandemic: thyroid nodules and cancer

Abstract: Health care settings, including nuclear medicine (NM) departments promptly adjusted their standard operating procedures to cope with the unprecedented crisis caused by COVID-19 pandemic. Nuclear thyroidology has adopted changes, predicated on a careful risk–benefit analysis, in order to prevent a potential spread of the virus while being at the same time effective, safe and preserving their quality of essential services. Since most thyroid nodules are benign, and malignant neoplasms are characterized by an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Since thyroid cancer has a good prognosis compared to other solid organ cancers, recent guidelines recommended that diagnosis and thyroid cancer surgery could be delayed during the COVID-19 pandemic [ 11 , 12 , 13 , 14 , 15 ]. However, due to delayed diagnosis and treatment during the pandemic, thyroid cancer tended to progress to worse pathologic status, such as extrathyroidal extension and lymph node metastasis, even if most thyroid cancers typically exhibited indolent behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Since thyroid cancer has a good prognosis compared to other solid organ cancers, recent guidelines recommended that diagnosis and thyroid cancer surgery could be delayed during the COVID-19 pandemic [ 11 , 12 , 13 , 14 , 15 ]. However, due to delayed diagnosis and treatment during the pandemic, thyroid cancer tended to progress to worse pathologic status, such as extrathyroidal extension and lymph node metastasis, even if most thyroid cancers typically exhibited indolent behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of COVID‐19‐related features (infection history and vaccination features) remains a poorly researched topic regarding the classification of thyroid nodules. From previously published studies, it seems that the pandemic has considerably impacted the diagnosis and treatment of thyroid nodules 32,33 . However, the impact does not appear to have significantly compromised the accuracy of diagnoses or affected the management.…”
Section: Discussionmentioning
confidence: 99%
“…Our COVID‐19 data, which shows the distribution of Bethesda‐I and Bethesda category II–VI results among patients with varying COVID‐19 histories, vaccine types, and booster doses, does not indicate a significant difference in the distribution based on these factors. According to the studies by Giannoula et al 32 and Vrachimis et al, 33 it has been suggested that delaying TFNAB for most asymptomatic thyroid nodules due to COVID‐19 does not negatively impact the outcomes in thyroid cancers, provided that symptoms and signs of urgent intervention are taken into account. The research by Rossi et al supports these conclusions, showing no difference in the diagnostic accuracy of TFNAB of thyroid nodules based on vaccination status and even during the pandemic 34 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations